ANALYTICAL STUDY ON DISTRIBUTION & GENDER PREDILECTION OF LIP PRINT PATTERN (Asian Journal of Medical Research and Health Sciences, 2026)
Fingerprint evidence is undoubtedly the most reliable and acceptable evidence till date in the court of law. But now a days, lip print patterns play an important role in identification of criminals especially when such obtained from crime scene related to sexual assaults. Lip print pattern can be collected from accused to compare with lip print evidences found in crime scene to straight-line the investigation. Due to the immense potential of lip prints as an effective method of identification an attempt has been made in the present work to analyse & classify the different types of lip prints in the study population. This study was conducted to determine the most common pattern in six quadrants of lip to evaluate variations in lip prints between males and females. The samples collected form 100 individuals which include 50 male and 50 female within age group of 19-30 years. Lip print patterns were obtained using lipstick and adhesive tape. The quadrant wise variation in lip print helps to establish identity even in partial evidences obtained from crime scene and for sex differentiation among population.